Track cycling sprinters` training progression over a three-month period - Ferguson, H.; Harnish, C.; Chase, J. G. (Journal of Science and Cycling, 2024)
There is a paucity of data on the progression of track cycling sprinters, and particularly the evolution of training and performance over a training cycle or season. Following our prior research showing strong relationships between sprint cycling power and endurance cycling power, we compared these relations over a 3-month period building towards a key event where maximal 30-s power was achieved. Our hypothesis is large improvements in power would come from training either for sprint maximal power or sprint maximal capacity, and this would be reflected in the data. A total of publicly available 25 datasets, over a 3-month period were used and broken into 1-month blocks. These data were plotted against the line of best fit for 30-s and 2-min power to assess if training towards the line led to better 30-s power, in contrast to focusing only on peak power. We observe the best performances came from riders who start below the 30-s vs 2-min power line of best fit, with greater capacity and ability to ride fast over a sprint series, and progressing towards focusing on specific power in the final block leading into a competition. These results support the hypothesis of combined capacity and power training based on rider-specific relationship to the line of best fit between these measures versus a strictly maximal power training focus.